A Clinico-dermatoscopic Study of Vulvar Dermatosis at Rural-based Tertiary Care Teaching Institute - A. Pragya Nair; Rutoo Vipulkumar Polra; Mauli M. Shah; Jinal Jainendrabhai Tandel; Priya K. Ghoghara; Shree Dhanani (Clinical Dermatology Review, 2024)
Introduction: The frequency and importance of vulval diseases are often underestimated due to the multifactorial nature of disease on the vulva. Dermoscopy can help provide clues for early diagnosis and insight into dermoscopic patterns. The present study was done with the objective to study the clinico-dermoscopic pattern of dermatosis and correlate the dermatoses with the age of the patient. Materials and Methodology: This was a prospective cross-sectional observational study conducted in the department of dermatology at a tertiary health care center over a period of 1½ year. All females with dermatosis affecting genital areas attending the skin outpatient department or ward were recruited after taking written consent. A detailed history was taken to collect demographic data. A thorough clinical examination and dermatoscopy were done. Descriptive statistics was used to depict the profile and dermatoscopic pattern. Results: Out of the 103 patients with vulvar dermatoses, 24 (23.30%) patients were in the age group of 41–50 years. A total of 43 (41.74%) patients had infective conditions, followed by 16 (15.53%) patients of papulosquamous group of disorders and 11 (10.67%) patients of eczema. Dermatoscopic findings had a surface scale in 40 (38.83%), vascular patterns in 22 (21.36%), red dots in 19 (18.45%), and structureless patterns in 13 (12.62%) with different vulvar dermatosis. In tinea cruris, out of 30 cases, 28 (93.33%) had surface scales, followed by 5 (16.67%) showing vascular pattern, whereas in lichen sclerosus et atrophicus, out of total of 10 cases, 8 (80%) had structureless pattern and 6 (60%) had vascular patterns. Discussion and Conclusion: Genital diseases represent a diagnostic challenge for clinicians. The use of dermoscopy improves the diagnostic accuracy by recognizing specific dermoscopic patterns. Limitation: Small sample size was the only limitation.